2023
DOI: 10.1037/trm0000389
|View full text |Cite
|
Sign up to set email alerts
|

Is young age a risk factor for PTSD? Age differences in PTSD-symptoms after Hurricane Florence.

Abstract: Age differences in posttraumatic stress disorder (PTSD) are widely researched, but findings remain inconclusive. The mixed findings may in part result from sampling participants exposed to different trauma types at different times. Here, we controlled for this issue by sampling participants exposed to the same devastating hurricane. A total of 1.5 months after Hurricane Florence (T1), we asked 174 adults living in two severely affected states to describe their hurricane experience and fill in measures of PTSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 92 publications
4
5
1
Order By: Relevance
“…Further, groups differed on CES, and CES was strongly correlated with PCL-5. As we previously found an age affect after controlling for CES (Kongshøj & Berntsen, 2022)-that is, contrary to our predictions-we added CES as a predictor both to control for this variability and to replicate the previous model. The final model thus consisted of two steps with age (at trauma vs. current) and retention interval in the first step and CES in the second.…”
Section: Resultscontrasting
confidence: 73%
See 3 more Smart Citations
“…Further, groups differed on CES, and CES was strongly correlated with PCL-5. As we previously found an age affect after controlling for CES (Kongshøj & Berntsen, 2022)-that is, contrary to our predictions-we added CES as a predictor both to control for this variability and to replicate the previous model. The final model thus consisted of two steps with age (at trauma vs. current) and retention interval in the first step and CES in the second.…”
Section: Resultscontrasting
confidence: 73%
“…For instance, Boals et al (2012) found young participants to consider their traumas more central than older participants, and this relationship mediated age differences in PTSD-symptoms, where younger participants displayed higher symptom levels. In contrast, in a study on hurricane victims, youth was associated with higher levels of PTSD-symptoms, but not due to differences in trauma centrality (Kongshøj & Berntsen, 2022). However, participants were generally not very impacted by the hurricane and did not rate the event as central to their life stories.…”
Section: Age At Study Versus Age At Traumamentioning
confidence: 89%
See 2 more Smart Citations
“…It is possible that younger individuals may be more vulnerable to developing PTSD due to their increased grey matter volume or that their brains may be more susceptible to changes associated with PTSD. Young age is one of the potential risk factors that play a role in PTSD and it has been suggested that the younger age increase vulnerability for PTSD [37].The result of a symptom-based study by Konnert and Wong have proposed the less severe symptoms for older veterans instead of young veterans with PTSD [3].As compare to our study, blastexposed veterans have been found to experience an age-associated decrease in the integrity of their white matter, which may contribute to the neurodegenerative effects of the blast. Inthis study comparing veterans who had been exposed to close-range blasts (within 410 meters) to peers matched for age and severity of PTSD symptoms, it was found that there was a signi cant relationship between the amount of time since the veterans' most severe blast and fractional anisotropy in certain regions of the brain.…”
Section: Results Subcortical Grey Volumementioning
confidence: 99%